Evaluasi Bahan Ajar Bahasa Arab: Prinsip dan Teknik Evaluasi di MTs Al-Fakhriyah : Evaluasi Bahan Ajar Bahasa Arab: Prinsip dan Teknik Evaluasi - Musyarrofah, Latifatul (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Arabic language teaching materials at MTs Al-Fakhriyah require careful evaluation to ensure their effectiveness in supporting the learning process. Purpose: The aim of this study is to evaluate Arabic teaching materials by examining the principles and evaluation techniques applied. Method: This research uses a literature review design with a concept analysis approach. Data were obtained from relevant books, journals, and educational documents. The study employed document analysis, interviews, surveys, questionnaires, and case studies as evaluation techniques. Evaluation criteria were based on material quality standards and learning success indicators. Results and Discussion: The findings show that systematic and measurable evaluation techniques play a significant role in enhancing the quality of teaching materials. These include aligning evaluation indicators with learning objectives and incorporating feedback mechanisms into material development. The study also highlights the need for continuous assessment to identify weaknesses and support pedagogical improvement. Conclusions and Implications: Applying structured evaluation principles improves Arabic language instruction effectiveness in MTs. These findings underline the importance of ongoing evaluation and suggest future research to optimize material development practices.